Khaki and Emerald Green - Taber, Nancy (Atlantis)

(untitled) (Mount Saint Vincent University, 2020)
A short story about a military woman struggling with family, career, and PTSD. Her perspective on her situation shifts when she visits the Canadian Museum of Human Rights with her young son.